Improved Survival with Immunotherapy but Lack of Synergistic Effect with Radiation for Stage IV Melanoma of the Head and Neck. Issue 10 (October 2019) - Babcock, Blake; Rodrigues, Medora; Kearns, Donovan; Solomon, Naveenraj; Reeves, Mark E.; Senthil, Maheswari; Garberoglio, Carlos A.; Namm, Jukes P.
Prospective randomized studies have demonstrated a survival benefit of immunotherapy in stage IV cutaneous melanoma. Some retrospective studies have hypothesized a synergistic effect of radiation and immunotherapy. Our objective was to identify whether there is a survival benefit for patients treated with radiation and immunotherapy in stage IV cutaneous melanoma of the head and neck (CMHN). The National Cancer Database was used to identify patients with stage IV CMHN between 2012 and 2014. These patients were stratified based on receipt of radiation and immunotherapy. Adjusted Cox regression was used to analyze overall survival. A total of 542 patients were identified with stage IV CMHN, of whom 153 (28%) patients received immunotherapy. Receipt of immunotherapy (hazard ratio [HR] 0.69, P = 0.02) and negative LNs (HR 0.50, P = 0.002) were independently associated with improved survival, whereas radiation conferred no survival benefit (HR 1.17, P = 0.26). Patients who received immunotherapy without radiation were associated with significantly improved survival compared with those who received immunotherapy with radiation ( P < 0.0001). However, of patients who received radiation, the addition of immunotherapy did not seem to improve survival ( P = 0.979). In stage IV CMHN, immunotherapy confers a 32 per cent survival benefit. The use of immunotherapy in patients who require radiation, however, is not associated with improved survival.